Choice or No Choice? Genuine or Fake Choice? – A Qualitative Study for Reflecting on Housing Choice - Betty Yung; Barbara Leung (Critical Housing Analysis)
This paper seeks to reflect on issues related to the nature of housing choice, drawing on qualitative empirical data collected in in-depth interviews. This paper discusses two perspectives related to housing choice, namely, the ‘market perspective of housing choice’ and the ‘perspective of housing choice for well-being’. The ‘market perspective of housing choice’ highlights that desirability generally increases with a greater range of housing choice as the housing supply increases till a climax is reached, after which a further expansion of housing choice may indicate an excess housing supply, which may not be advantageous and home-buyers may instead ‘decide not to choose or buy’. The ‘perspective of housing choice for well-being’ reveals that choice in the housing arena is often viewed as a means to eventual well-being, rather than as an end in itself. Housing choice is ‘genuine’ and ‘meaningful’ if there are meaningful and significant options among a few desirable housing alternatives. ‘Fake housing choice’ involves having to choose from among housing options that are all generally bad.